2005
DOI: 10.1063/1.2136875
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of second-harmonic generation from isotropic liquid interface: Broken Kleinman symmetry of neat air/water interface from dipolar contribution

Abstract: It has been generally accepted that there are significant quadrupolar and bulk contributions to the second harmonic generation (SHG) reflected from the neat air/water interface, as well as common liquid interfaces. Because there has been no general methodology to determine the quadrupolar and bulk contributions to the SHG signal from a liquid interface, this conclusion was reached based on the following two experimental phenomena. Namely, the broken of the macroscopic Kleinman symmetry, and the significant tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 92 publications
(172 reference statements)
3
48
0
2
Order By: Relevance
“…Non-resonant SHG provides orientational measurement of the non-straddle-type of interfacial water molecules (Zhang et al, 2005). We are working far from any resonant second-order susceptibility χ NR effect is ignored since we do not track ion adsorption at the interface (Ong et al, 1992).…”
Section: Materials and Setupmentioning
confidence: 99%
“…Non-resonant SHG provides orientational measurement of the non-straddle-type of interfacial water molecules (Zhang et al, 2005). We are working far from any resonant second-order susceptibility χ NR effect is ignored since we do not track ion adsorption at the interface (Ong et al, 1992).…”
Section: Materials and Setupmentioning
confidence: 99%
“…Then, one has [35,40] In the previous study, we showed that the contributions from the ions and from the electric field induced SHG were negligible for the non resonant SHG signal from the electrolyte aqueous solution surface. Therefore, only the contribution from the interfacial water molecules need to be considered.…”
Section: Theoretical Background For the Shg Data Treatmentmentioning
confidence: 99%
“…For molecules with the C 2v symmetry, such as the water molecule, there are seven nonzero microscopic polarizability tensor elements β ijk (i, j, k = a, b, c) in molecular coordinates system (a, b, c): namely, β ccc , β caa , β cbb , β aca , β aac , β bcb and β bbc , with β aca = β aac and β bcb = β bbc for the SHG process. When the optical frequency is far below the resonance, β ccc is usually negligible, by defining R = (β caa + β cbb )/(β aca + β bcb ), one has, [35,40] …”
Section: Theoretical Background For the Shg Data Treatmentmentioning
confidence: 99%
“…[23,52] In these studies, we demonstrated that the non-resonant SHG signal was originated only from the electronic responses of the hydrogen bonded water molecules with the orientationally ordered structures at these electrolyte aqueous surfaces. [53] In the SFG-VS measurement, surface water molecules with different hydrogen bonding structures exhibit clearly different vibrational spectral features. However, the non-resonant SHG signal from these surfaces is the measurement of the whole water surface layer without discrimination on the surface water molecules in different hydrogen-bonding configurations.…”
mentioning
confidence: 99%